Different treatment regimens in breast cancer visceral crisis: A retrospective cohort study - Yang, Ruohan; Lu, Guanyu; Lv, Zheng; Jia, Lin; Cui, Jiuwei (Frontiers in Oncology, 2022)
Objective: Breast cancer visceral crisis (VC) is caused by excessive tumor burden leading to severe organ dysfunction with poor prognosis. Traditional chemotherapy reduces the quality of life of patients without significantly improving survival. The aim of this study was to investigate the clinical characteristics of patients with visceral crisis and the prognosis by using different treatment options. Methods: According to the 5th European School of Oncology (ESO)-European Society for Medical Oncology (ESMO) international consensus guidelines for advanced breast cancer guidelines (ABC 5), patients who treated in the First Hospital of Jilin University from 2018 to 2022 and diagnosed with breast cancer VC were retrospectively analyzed. The analysis focused on the characteristics of the patients, the treatment regimens and prognosis. Results: A total of 133 patients were included in this study. As for metastasis breast cancer subtype, 92（69.18%）were hormone receptor (HR) positive, Human Epidermal Growth Factor Receptor 2(HER-2) negative, 20（15.04%）HER-2 overexpression and 21 (15.78%) triple negative. All patients had a mOS of 11.2 months (1.1 – 107.8 months). In different types of visceral crisis, the mOS of bone marrow metastases (BMM) was 18.0 months (2.0-107.8 months) , Diffuse liver metastases (DLM) was 8.1 months (1.3-30.2 months) and 9.0 months (1.2-53.8 months) in Meningeal metastasis (MM). In ninety-two HR+, Her-2-patients using different treatment regimens, mOS was 6.2months (1.2 – 29.8months) in the chemotherapy group while 24.3 months (3.1 – 107.8 months) in the endocrine therapy (ET) group. Multivariate cox regression analysis suggested that ECOG scores and type of VC were associated with survival. Conclusion: Prognosis was varying in different type of VC. Patients with BMM had the best prognosis, and DLM had the worst. As treatment options continue to progress, our retrospective study showed a significant prolongation of OS in patients with VC compared to previous studies.